THE INDIGENOUS PEOPLE OF BIAFRA AGITATION AND THE FUTURE OF THE NIGERIAN STATE - EGUGBO, Chuks Cletus (Social Science Research, 2021)
This paper examines the nature of the Nigerian state with regard to the centrifugal forces threatening to tear it apart. Nigeria is made up of over three hundred (300) ethnic groups. These ethnic groups were existing independence of one another prior to the colonial rule. These diverse and multiple ethnic groups were brought together under one country known as Nigeria. Few years after independence, forces of disunity and disintegration started rearing their heads to the extent that there was a civil war in the country between 1967 and 1970. After the civil war, events in the country have tended to prove that the Igbos of the South-Eastern part of the country seem to be marginalized in the socio-political and economic scheme of things in the country. This situation necessitated the agitation for the sovereign state of Biafra by the Indigenous People of Biafra. The agitation by IPOB actually brought to the fore the defects in the structure and composition of the Nigerian state to the extent that the ‘Afenifere’, a Yoruba socio-cultural group, Middle-belt and the South-South part of the country started demanding for the restructuring of the Nigerian state to the extent that all parts of the country would be made to have a sense of belonging in the Nigerian project. Development of Nigeria would continue to be a distant dream if issues of ethnic domination and marginalization are not resolved. This paper recommends the restructuring of the Nigerian state to give all sections sense of belonging as well as constitutional amendment to provide for rotational presidency along the six geopolitical zones, such should also apply to states and local governments as well as adherence to the principle of rule of law, accountability and transparency in governance.